Impact of secondary care financial incentives on the quality of physical healthcare for people with psychosis: a longitudinal controlled study. (December 2019) - Crawford, Mike J.; Huddart, Daniel; Craig, Eleanor; Zalewska, Krysia; Quirk, Alan; Shiers, David; Strathdee, Geraldine; Cooper, Stephen J.
Abstract : Background: Concerns have repeatedly been expressed about the quality of physical healthcare that people with psychosis receive. Aims: To examine whether the introduction of a financial incentive for secondary care services led to improvements in the quality of physical healthcare for people with psychosis. Method: Longitudinal data were collected over an 8-year period on the quality of physical healthcare that people with psychosis received from 56 trusts in England before and after the introduction of the financial incentive. Control data were also collected from six health boards in Wales where a financial incentive was not introduced. We calculated the proportion of patients whose clinical records indicated that they had been screened for seven key aspects of physical health and whether they were offered interventions for problems identified during screening. Results: Data from 17 947 people collected prior to (2011 and 2013) and following (2017) the introduction of the financial incentive in 2014 showed that the proportion of patients who received high-quality physical healthcare in England rose from 12.85% to 31.65% (difference 18.80, 95% CI 17.37–20.21). The proportion of patients who received high-quality physical healthcare in Wales during this period rose from 8.40% to 13.96% (difference 5.56, 95% CI 1.33–10.10). Conclusions: The results of this study suggest that financial incentives for secondary care mental health services are associated with marked improvements in the quality of care that patients receive. Further research is needed to examine their impact on aspects of care that are not incentivised.